Is It Possible to Apply Multidimensional Graphical Methods in The Teaching and Learning of Economics? - Mario Arturo Ruiz Estrada (Contemporary Economics, 2013)
This article explores the effectiveness of applying a new multidimensional graphical method to the teaching and learning of economics. In essence, the paper extends the significance of multi-dimensional graphs to study any economic phenomenon from a multidimensional perspective. The paper proposes the introduction of a new set of multidimensional coordinate spaces that should clearly and logically propose the effective visualization of complex and dynamic economic phenomena into the same graphical space and time with which the effectiveness of multidimensional graphs for real practical purposes can be evaluated. From the analyses carried out, which are based on both primary and secondary data sources, the article argues that multidimensional graphs can actually be evaluated to understand the degree of their effectiveness in visualizing economic problems affecting society on different levels.
Keywords: A22; A23; CO2; B41; E00; 330; multidimensional graphs; economics teaching; GDP graphical analysis